Frustrated Lewis pairs incorporating the bifunctional Lewis acid 1, 1′-fcB(C6F5)22: reactivity towards small molecules. Issue 5 (11th January 2018) - Tirfoin, Rémi; Gilbert, Jessica; Kelly, Michael J.; Aldridge, Simon
Abstract : Applications of the bifunctional Lewis acid 1, 1′-fcB(C6 F5 )2 2 in FLP chemistry are described, including reactions towards H2 O, NH3, CO2 and cyclohexylisocyanate. Abstract : Applications of the bifunctional ferrocenediyl Lewis acid 1, 1′-fcB(C6 F5 )2 2 in frustrated Lewis pair (FLP) chemistry are described. The coordination (or otherwise) of a range of sterically encumbered C-, N- and P-centred Lewis bases has been investigated, with lutidine, tetramethylpiperidine, PPh3, P t Bu3 and the expanded ring carbene 6Dipp being found to be sterically incapable of coordinate bond formation. The chemistry of a range of these FLPs in the presence of H2 O, NH3, CO2 and cyclohexylisocyanate (CyNCO) has been investigated, with the patterns of reactivity identified including simple coordination chemistry, E–H bond cleavage and C–B insertion.